The mucosal and systemic immune responses in chickens orally immunised with Campylobacter jejuni antigen entrapped in poly-lactide-co-glycolide microparticles - Noor, Susan Maphilindawati (Indonesian Journal of Animal and Veterinary Sciences, 1998)
An oral immunisation in chickens with antigen entrapping in biodegradable microparticles was evaluated in order to achieve optimal antibody responses following oral vaccination. This study was adapted to Campylobacter jejuni antigen in chickens to observe its stimulation both mucosal and systemic immune responses. A group of 5 embryonated chicken eggs was immunised with heat-killed C. jejuni entrapped in poly-lactide-co-glycolide (PLG) microparticles at day 17 of incubation deposited into the amniotic fluid. Seven days after hatching the chickens were oral boostered, these was design to as Group A. In the Group B, each embryonated egg was immunised with soluble C. jejuni as in the same as Group A. Immune responses of post vaccination were observed at day-14, the humoral immunity was evaluated with an ELISA and whereas mucosal antibody response was detected by fluorescent histology. The serum IgG and IgA antibody responses, and also the bile and intestinal scrapping IgA antibody responses to campylobacter in Group A were significantly higher than those of the soluble antigen of Group B (P<0.05). Total number of immunoglobulin-containing cells for IgG, IgM, and IgA isotypes in the ileum in Group A chickens were also significantly higher than those of Group B (P<0.05) but was not in the duodenum and spleen. Key words : Campylobacter jejuni, poly-lactide-co-glycolide microparticles, oral immunisation, chickens